Chlorophyll meter for the evaluation of potato N status - Giletto, Claudia Marcela (2013)
Here, we propose a new approach to determine the level of plant N nutrition, based on the relationship between chlorophyll meter (CM) readings and total biomass in potato plants. The objectives of this work were i) to determine the critical curve CM (CMc) readings; ii) to establish the relationship between N nutrition index of CM (NNICM), and relative tuber yields (RY), and iii) to establish the crop N required (NR). The experiments were carried out during four growing seasons. The cultivar Innovator was planted in a randomized complete block design with three replications and four N treatments (N0, N1, N2 y N3) to cover the range from deficient through surplus N. The CM reading was assessed with the Minolta SPAD 502 at different times during each growing season. The NNICM was determined as the ratio between the actual CM reading (CMa) and the CMc. The NR was determined as the difference between actual N uptake and the critical N uptake, divided the N utilization efficiency. The CMc for cultivar innovator was determined [CMc = 51.4 W (Mg ha_1)−0.13; R2 = 0.83]. The NNICM ranged from 0.78 to 1.17. The relation between RY and NNICM was expressed as a linear-plateau function. For NNICM ≥0.9, the RY was near 98.0 %, whereas for NNICM below 0.9, the RY decreased [RY = 7.73 + 100.0 NNICM; R2 = 0.55]. The relationship between the observed N uptake and the estimated N uptake values showed positive significant associations (p < 0.0001). We conclude that the CM reading can be used as an easy and fast tool to predict NR in potato plants under field conditions during the vegetative growth period.